Mountain rescue - Owens, Sandra (Owens, Sandra. Operation K-9 Brothers Series, 2021)
The sole witness to a murder, stuntwoman Rachel Denning found the perfect hideout until a man appears in her remote cabin. But Dallas Manning isn't there to kill her, he's there to recover in his retreat.